2006
DOI: 10.1182/blood-2006-06-027631
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 induces hepcidin expression through STAT3

Abstract: Iron homeostasis is maintained through meticulous regulation of circulating hepcidin levels. Hepcidin levels that are inappropriately low or high result in iron overload or iron deficiency, respectively. Although hypoxia, erythroid demand, iron, and inflammation are all known to influence hepcidin expression, the mechanisms responsible are not well defined. In this report we show that the inflammatory cytokine interleukin-6 (IL-6) directly regulates hepcidin through induction and subsequent promoter binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
599
6
22

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 834 publications
(652 citation statements)
references
References 30 publications
25
599
6
22
Order By: Relevance
“…7 This study underlines the Iron regulation during acute-phase reaction N Sheikh et al differences between the two animal models and indirectly confirms that IL-6 is the major player in modifying iron metabolism under acute-phase condition. 13,[38][39][40][41][42][43][44] Most studies to date have shown that the transcriptional changes in the Hepc gene expression parallel the changes in serum iron concentration; however, limited studies have been performed to show the changes in the concentration of this important hormone in the serum. [45][46][47][48] Intramuscular TO injection induced significant decrease of the serum iron concentration without a significant change in serum proHepc concentration.…”
Section: Discussionmentioning
confidence: 99%
“…7 This study underlines the Iron regulation during acute-phase reaction N Sheikh et al differences between the two animal models and indirectly confirms that IL-6 is the major player in modifying iron metabolism under acute-phase condition. 13,[38][39][40][41][42][43][44] Most studies to date have shown that the transcriptional changes in the Hepc gene expression parallel the changes in serum iron concentration; however, limited studies have been performed to show the changes in the concentration of this important hormone in the serum. [45][46][47][48] Intramuscular TO injection induced significant decrease of the serum iron concentration without a significant change in serum proHepc concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have provided information regarding the part of the promoter required for IL-6 to induce hepcidin expression through the mediation of STAT3 [11]. However, the mechanism by which iron stimulates hepcidin expression still remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…2A, inset). Earlier studies concentrated on the regulation of HAMP expression at the transcriptional level (12)(13)(14)(15). The effect of fatty acids on HAMP transcription was examined by luciferase reporter assays in HepG2 cells transfected with pGL-3 Basic vector harboring the 1.5-kbp HAMP promoter (HAMP PromLuc).…”
Section: Regulation Of Hamp Mrna Expression By Fatty Acids Inmentioning
confidence: 99%
“…Inflammatory cyto-kines, serum transferrin, erythropoiesis, and hepatic iron stores have all been shown to stimulate the promoter activities of both human and mouse hepcidin genes via the activation of specific transcription factors (12)(13)(14)(15). It should, however, be noted that other iron-regulatory proteins, transferrin receptor 1 and ferritin, are regulated at the post-transcriptional and translational level, respectively, by iron-regulatory RNA-binding proteins (IRPs), IRP1 and IRP2 (16).…”
mentioning
confidence: 99%